Terpene mixtures and metabolic syndrome in the US general population: exploring the mediating role of insulin resistance - Dan’an Wang; Wei Zhang; Zhenni Zhao; Duanbin Li; Yuan Fang; Zijie Wang; Jingyi Lv; Yi Luan; Wenbin Zhang (BMC Public Health)
Abstract Background Terpenes have been shown to have an effect on metabolic status. However, it is unclear how they are associated with the metabolic syndrome (MetS) and whether insulin resistance (IR) mechanisms are involved. Methods This cross-sectional study included data from the National Health and Nutrition Examination Survey (2013–2014). Serum terpenes (α- pinene, β- pinene, and limonene) were quantified by gas chromatography-tandem mass spectrometry. MetS was diagnosed by lipid, glucose, blood pressure, and waist circumference criteria. IR status was assessed using the homeostasis model assessment of insulin resistance (HOMA-IR) model and triglyceride-glucose index. Regression analysis models, mixed-effects models (weighted quantile sum regression models, quantile g-computation and Bayesian Kernel machine regression models), and mediation analysis were used for analysis. Results Among 1563 U.S. general population (mean age 39.0 years), 447 (28.6%) had a diagnosis of MetS, and the median concentration was 0.08 ng/mL for α- pinene, 0.08 ng/mL for β- pinene, and 1.18 ng/mL for limonene. The terpene mixture showed positive joint association with MetS (OR = 1.454, 95%CI = 1.153, 1.833) and HOMA-IR (β = 0.569, 95%CI = 0.196, 0.942), with limonene contributing relatively large weights in both MetS (41.1%) and HOMA-IR (68.9%). Furthermore, HOMA-IR was positively associated with MetS (OR = 2.299, 95%CI = 1.888, 2.817) and its diagnostic components. When identified as a mediator, HOMA-IR accounted for approximately 15.8%, 20.0%, and 14.3% of the indirect effects between terpenes (α- pinene, β- pinene, and limonene) and MetS, respectively. The results were consistent when the IR biomarker was replaced by triglyceride-glucose index. Conclusion Serum terpenes were positively associated with MetS, which might be partially mediated by the mechanism of IR.